Not all built the same? a comparative study of electoral systems and population health - Patterson, Andrew C. (My University, 2017)
Much literature depicts a worldwide democratic advantage in population health. However, less research compares health outcomes in the different kinds of democracy or autocracy. In an examination of 179 countries as they existed between 1975 and 2012, advantages in life expectancy and infant health appear most reliably for democracies that include the principle of proportional representation in their electoral rules. Compared to closed autocracies, they had up to 12 or more years of life expectancy on average, 75% less infant mortality, and double the savings in overall mortality for most other age groups. Majoritarian democracies, in contrast, did not experience longitudinal improvements in health relative to closed autocracies. Instead their population health appeared to be on par with or even superseded by competitive autocracies in most models. Findings suggest that the principle of proportional representation may be good for health at the national level. Implications and limitations are discussed.
Keywords: autocracy; democracy; elections; infant mortality; life expectancy